What are the metabolic precursors which increase the risk of pre-eclampsia and how could these be investigated further. (December 2017) - Myers, Jenny E.
Abstract: Several maternal and pregnancy characteristics have been associated with an increased risk of preeclampsia in epidemiological studies. This review discusses metabolic risk factors in particular and their interaction with other maternal and/or pregnancy characteristics. Examples of research studies that have used data from women with specific characteristics or explored the interaction between risk factors are discussed. Suggestions for future research using large data sets and incorporating knowledge of cardiovascular disease and other metabolic diseases are also highlighted. Highlights: Obesity and nulliparity account for the largest population risk of preeclampsia. Low PlGF in early pregnancy is more strongly associated with preeclampsia in obese women. There are interactions between obesity and other characteristics which amplify the risk of preeclampsia e.g. ART, ethnicity.